6(1-2x)-x=-46

Simple and best practice solution for 6(1-2x)-x=-46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(1-2x)-x=-46 equation:


Simplifying
6(1 + -2x) + -1x = -46
(1 * 6 + -2x * 6) + -1x = -46
(6 + -12x) + -1x = -46

Combine like terms: -12x + -1x = -13x
6 + -13x = -46

Solving
6 + -13x = -46

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -13x = -46 + -6

Combine like terms: 6 + -6 = 0
0 + -13x = -46 + -6
-13x = -46 + -6

Combine like terms: -46 + -6 = -52
-13x = -52

Divide each side by '-13'.
x = 4

Simplifying
x = 4

See similar equations:

| B-17=-38 | | 6+2x=5-(7x) | | J+13=37 | | a^2+4ab+4b^2=0 | | M+(-10)=(-2) | | -3a+8=2 | | 4x-3y=52 | | (-17)=(-9)+q | | f(x)=a^3-3a^2-9 | | 2.25=3/4(b-5) | | 17+n=4 | | 6x-x^2+16= | | (-22)+j=(-24) | | 72.8=7(m+3.1) | | 4x+23=75 | | (2c+9)x(c+5)= | | 3[m-1.2]=9 | | h-8+2(h-8)=72 | | 47=19-4x | | 39+x=30+2x | | R-20+4=18 | | 1521=39p+390 | | M+52=53 | | 14y+6(4-8y)= | | y-1/3x=0 | | D-35=50 | | 10(0.6x+4)=10(0.3x+7) | | 2x/(x-3)=8 | | 1521=39(p+10) | | A-3=24 | | 10=17+b | | 3v+12=63 |

Equations solver categories